Projecting of Urban Transport Infrastructure Considering the Human Factor - Natalia Davidich; Andrii Galkin; Vladimir Sabadash; Igor Chumachenko; Tatyana Melenchuk; Yurii Davidich (Communications - Scientific letters of the University of Zilina, 2020)
Projecting of urban transport infrastructure, which forms a comfortable habitat and development of territories, is impossible without forecasting the parameters of transport and passenger flows. These parameters are formed under the influence of the subjective choice of urban residents on the routes along the road and route network. The study aims to identify factors affecting the distribution of transport and passenger flows through the existing urban transport network. It is revealed that the gravity function of employees of city-forming enterprises, which determines the emergence and absorption of transport and passenger flows of the city districts, can be described by parameters of urban structure, socio-economic factors and parameters that characterize zones of residence and main area of employment. The developed model was tested on real data from Kharkov - the second largest city in Ukraine.